Uninformative Anchors Have Persistent Effects on Valuation Judgments. Issue 3 (13th February 2019) - Yoon, Sangsuk; Fong, Nathan
Abstract : Anchoring effects influence a wide range of numeric judgments, including valuation judgments, such as willingness‐to‐pay (WTP). However, prior research has not established whether anchoring only temporarily distorts responses or exerts persistent influence on preferences. This article presents three incentive compatible experiments examining the long‐term effects of random anchoring on WTP. Study 1 evaluated the persistence of anchoring effects over long durations, and showed that the strength of the effect decayed but did not disappear completely even 8 weeks later. In Study 2, a random anchor significantly influenced WTP after one week, regardless of whether WTP was also elicited immediately following the anchoring procedure, showing that consistency motivations do not account for persistence of anchoring effects. Study 3 showed relatively low anchors resulted in more stable valuations, compared with participants who reported WTP with no anchoring procedure. Together with the pattern of decay over time in Study 1, this suggests that anchoring facilitates the "imprinting" of valuation judgments for later retrieval. These studies show that anchoring effects can lead to lasting changes in valuation judgments, providing the first demonstration of long‐term persistence of constructed preferences as a result of an uninformative and arbitrary manipulation.